Responding to patient deterioration: a medical records analysis - Mohamed Ludin, Salizar; Ruslan, Rusila (Kulliyyah of Nursing, International Islamic University Malaysia, 2018)
Objective: This paper reports the medical record analysis findings to identify nurses and junior doctors risk assessment and response to the incidence of deteriorating patient in general ward. Methods: A medical records analysis was conducted at a medical ward in one Malaysian hospital. Patients that were admitted for more than 24 hours and scored at least 3 points on the Modified Early Warning Sign (MEWS) assessment with their last 24 hours parameters calculated and nurses and junior doctor’s responses were analysed retrospectively. Results: Out of 200 records obtained, only 10 patients’ medical records met the study inclusion criteria. Three main themes were evident in the study, namely ‘track and trigger’, ‘hierarchical intervening’ and ‘attitude’. Conclusion: This study demonstrates that some nurses and junior doctors experience difficulties in effectively responding to patient deterioration which often occurs at a critical juncture. This study highlights factors which need to be addressed to increase patient safety and improve medical outcomes during hospitalization.